Scinetific Problems of Modern Approach of Net Present Value - Illés, Mária (Theory, Methodology, Practice – Review of Business and Management, 2007)
There are some scientific questions of NPV analysis, which has not been worked up. Would be useful for practice to explore the special inherence of the NPV method for making financial and management decisions, as well as for the different cash flow projects (typical that is “orthodox” and non typical that is “unorthodox” cash flow series). There is not cleared up scientific background of the question, why is not equal the total cost of capital for equity and for debt. Net present value is a well-known category of economics and everyday management practice. Practical experiences show when companies use net present value calculation several problems emerge, wrong applications are general as well as misinterpreting. A large part of these can be due to the characteristics of the literature background. This paper intends to reveal besides these characteristics the directions of further economic research works on this topic. Net present value calculation has also become part of the economic school-material in the Hungarian higher education since the second half of the 60’s. In this period we could have met several interpretational and applicational mistakes, which was typical not only in the Hungarian but also in the international literature.